Amidst the flow: biographical narratives, social trajectories, and urban itineraries of crack users in São Paulo - Reichert, Richard Alecsander (Ethics International Press Ltd, 2024)
This book presents data and discusses the results of research conducted on crack cocaine consumption and other drug use in the city of São Paulo, Brazil, specifically in the area commonly referred to as "Cracolândia" (Crackland). This context is marked by high social vulnerability, rife with numerous inequalities, violence, and human rights violations. The work describes the living conditions of individuals in this setting, narrating their social trajectories, urban itineraries, motivations for substance use, perspectives, and life projects